G324 Expression of neurones and neuronal precursors in the transition zone of short segment hirschsprung's disease. (25th October 2020) - Doherty, J; Chhabra, S; Smith, M; Edgar, D; Almond, S; Kenny, SE; Wilm, B
Abstract : Aims: Hirschprung's Disease (HSCR) is a congenital disorder of dysfunctional enteric nervous system (ENS) development, resulting in distal aganglionosis of the bowel. The cellular composition of the transition zone (TZ), the region between the distal aganglionic bowel and normally innervated ganglionic bowel, is not well understood. Some children have resectional surgery in which TZ bowel is left in situ with variable effects on functional outcome. Understanding the cellular anatomy of this region may aid in understanding the aetiology of HSCR and the effects of TZ pull-through on outcome, in addition to permitting the development of safe and effective use of ENS progenitor cells as therapy. This work aimed to characterise the TZ of short segment HSCR bowel, by assessing the expression of ENS and neuronal markers by immunofluorescence and quantitative PCR(qPCR). Methods: Human bowel was collected following a pull-through procedure in four patients with short segment HSCR. Protein expression of ENS and neuronal markers (p75, SOX10, PHOX2b, Hu and GLUT1) in ganglionic, TZ and aganglionic region of the bowel were visualised through immunofluorescence and mRNA levels of the corresponding markers were quantified using qPCR. Results: Immunofluorescence analysis showed a gradual loss of SOX10, PHOX2b and Hu protein in the lower TZ and absence in the aganglionic region. However, generally the marker expression presented with inter-patient variability within the TZ. By contrast, GLUT1 was highly expressed in the perineurium of thickened nerve trunks, characteristic of the aganglionic region. Perineurial structures positive for GLUT1 were also visualised in the TZ, but to a lesser extent than the aganglionic region. This observation corresponded with a decrease in mRNA levels of p75, SOX10, PHOX2b and Hu from the ganglionic to the aganglionic region and an increase in GLUT1. Conclusion: This work displayed a trend of decreasing number of cells expressing ENS and neuronal markers from the ganglionic to aganglionic region, through the TZ. However, our analysis reveals inter-patient variability in the cellular composition of HSCR bowel, especially in the TZ. Possibly explaining the variable functional outcome for HSCR children with TZ pull-through.